A Comparative Study of Interpersonal Relationship in Confucian and Hebrew Classics - He, Hua (Cultural and religious studies, 2021)
Both Confucian and Hebrew classics remain an everlasting heritage for their nations and the world. Wisdom from both classics stresses the importance of interpersonal relationships in constructing the social order. This paper, through a comparative study, analyzes similar teachings and rituals concerning two prominent interpersonal relationships—marital bond and parent-child relation. It is found that in these two interpersonal relationships, both wisdom highlight the significance of these bonds, define clear boundaries and roles, and provide ethical warnings in these relations. This study contributes to the cross-cultural investigation of ancient Chinese and Hebrew wisdom in that human nature is embedded with similar hope for order, quality, and glory, so mutual understanding and acceptance is essential in promoting a globalized dialogue and critical view of cultures. Suggestions are provided for further research.